Education and purification in Da'wah Sufi methods: A reference to the reform method Syeikh Ahmad Zarruq's: A case study (846 AH – 899 AH) / Abdalsalam Ibrahim Hamad Gadalla - Abdalsalam Ibrahim, Hamad Gadalla (2022)
Reforming individuals and societies depends greatly on the extent they are connected to Education and Purification. Therefore, this study aimed to examine, generally, the importance of Education and Purification and, in particular, its significance in the Sufi Dawah to highlight the main characteristics of Sufi Dawah methodology and rectify some contemporarily applied methodologies. The research also aimed to examine the fundamentals of Education and Purification methodology of in order to adopt it in strengthening Dawah methodologies with scholarly precepts that could uplift the Sufi Dawah methodology in particular, and the Dawah methodology in general. The study also included the main attributes of the Dawah methodology of Ahmad Zarruq which specified the characteristics of his Education and Purification methodology. The Sufi school has contributed many theoretical and practical solutions in relation to Education and Purification. Nonetheless, Sufism has suffered many deviations when some Sufists didn’t follow the Education and Purification teachings of Sufi scholars. To address this, the researcher opted to choose an exemplary case of reformatory Dawah i.e., the case of Ahmad Zarruq. This was due to his conspicuous role in the reform and revival in relation to Sufi Dawah methodologies. To highlight the main characteristics of his methodology in Education and Purification, the researcher examined Ahmad Zarruq's writings and deduced from them his methodology of Education and Purification. The study contained the fundamentals of his Education and Purification methodology which was deduced from the Quran and Sunnah. This methodology is distinguished by its ability to address many issues realted to Education and Purification in the Sufi school. the researcher adopted the deductive, critical, comparative and deductive method, methodology among the findings of which: The researcher realized the great importance of Education and Purification in building individuals and societies. Also, Sheikh Ahmad Zarruq has established his methodology on firm precepts from the Quran and Sunnah. He rarely mentions an issue without supporting it with its evidence from the Quran or Sunnah. The Dawah methodology of Ahmad Zarruq is distinguished by its comprehensiveness as it establishes the foundation evidence from the Quran or Sunnah. The Dawah methodology of Ahmad Zarruq is distinguished by its comprehensiveness as it establishes the foundation.